Engineered Extracellular Vesicles Loaded With miR-124 Attenuate Cocaine-Mediated Activation of Microglia - Chivero, Ernest T.; Liao, Ke; Niu, Fang; Tripathi, Ashutosh; Tian, Changhai; Buch, Shilpa; Hu, Guoku (Frontiers in Cell and Developmental Biology, 2020)
MicroRNA-124 (miR-124), a brain-enriched microRNA, is known to regulate microglial quiescence. Psychostimulants such as cocaine have been shown to activate microglia by downregulating miR-124, leading, in turn, to neuroinflammation. We thus rationalized that restoring the levels of miR-124 could function as a potential therapeutic approach for cocaine-mediated neuroinflammation. Delivering miRNA based drugs in the brain that are effective and less invasive, however, remains a major challenge in the field. Herein we engineered extracellular vesicles (EVs) and loaded them with miR-124 for delivery in the brain. Approach involved co-transfection of mouse dendritic cells with Dicer siRNA and RVG-Lamp2b plasmid to deplete endogenous miRNAs and for targeting the CNS, respectively. Mouse primary microglia (mPm) were treated with purified engineered EVs loaded with either Cy5-miR-124 or Cy5-scrambled miRNA oligos in the presence or absence of cocaine followed by assessing EV uptake and microglial activation. In vivo studies involved pretreating mice intranasally with engineered EVs followed by cocaine injection (20 mg/kg, i.p.). mPm exposed to EV-miR-124 exhibited reduced expression of miR-124 targets – TLR4 and STAT3 as well as ERK-1/2 and Iba1. In cocaine administered mice, EV-Cy5-miR-124 delivered intranasally were detected in the CNS and significantly reduced the expression of inflammatory markers TLR4, MYD88, STAT3 and NF-kB p65 while also downregulating the microglial activation marker, Iba1. Collectively, these findings suggest that engineered EVs can deliver miR-124 into the CNS, thereby alleviating cocaine-mediated microglial activation. Manipulating EV miRNAs can thus be envisioned as an efficient means for delivery of RNA-based therapeutics to target organs.